MENINGKATKAN KETERAMPILAN MENGUNGKAPKAN MONOLOG DESCRIPTIVE LISAN SEDERHANA YANG BERTERIMA SISWA KELAS VIIA SMP NEGERI 1 AIR KUMBANG MENGGUNAKAN SISTIM ICARE - Chandra, Edy (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2017)
Abstract : The Action Classroom Research is an attempt to improve the Seventh A Class students? skills in expressing Simple Descriptive Monologue at SMP Negeri 1 Air Kumbang, Banyuasin. This study used three cycleswith ICARE System through five stepswhich are Introduce, Connect, Apply, Reflect, and Extend. The data were taken from observation and questionnaire for qualitative data and individual assessment report for quantitative data. Finally, it was found that ICARE system could (1) improve the students? skill in expressing simple descriptive monologue, (2) improve the students spoken English with correct pronunciation, and (3) Improve the students? courage in expressing simple descriptive monologue.